Mechanical Behavior of MTMoCr under High Temperature and High Strain-rate - Jingkui Ruan; Zhengwei Dong (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
MTMoCr is a kind of Mo-Cr alloy cast iron often used to make automobile panel dies. To study high-speed machining process of automobile panel dies, the material’s elastic modulus and rupture critical values of MTMoCr at 20℃-800℃ were studied based on the high temperature elongation test. The material’s stress-strain diagram at various temperatures set-points (20℃-500℃) and various strain-rates (500/s-5000/s) were studied and the dynamic tensile yield strength values were obtained by dynamic SHPB (Split Hopkinson Pressure Bar) high-speed compression test. The experimental results indicate that MTMoCr has heat resistance and its behavior is between toughness and brittleness materials. Its toughness is enhanced with temperature increasing. The strain-rate strengthening effect prevails over temperature softening effect. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2064